Sistem Pendukung Keputusan Pemilihan Program Studi Calon Mahasiswa Menggunakan Weighted Product (WP) - Novianti Indah Putri; Yogi Saputra; Siti Nurhayati; Dzariyati Dzarwah (TEMATIK, 2023)
The suitability of study programs to aspects of academic talent and general knowledge will greatly support the comfort of prospective students later when they are already students, the selection of study programs often does not consider the real side of the suitability of academic values, most prospective students will choose what they are interested in at that time, which impacts these students will tend not to be able to develop what is really there in them, interest alone is not enough of course there needs to be adjustments to what strengths a prospective student has. The decision-making system using the weighted product method will greatly help prospective students determine the majors they will take after becoming students. This decision-making system will illustrate how the scores from the test obtained by prospective students can help provide an overview of how suitable the student is with the study program he is interested in, this simple system uses the Weighted Product (WP) method, one of the SPK methods included in Fuzzy Multiple Attribute Decision Making (FMADM).